2018
DOI: 10.1002/smr.1981
|View full text |Cite
|
Sign up to set email alerts
|

Approaches, success factors, and barriers for technology transfer in software engineering—Results of a systematic literature review

Abstract: Introduction: Technology transfer aims at supporting the transfer of results from software engineering research from academia to industrial application.Objective: This paper reports on the current state of technology transfer in software engineering.Method: We conducted a systematic literature review, in which we investigated 3070 papers. We identified in total 70 relevant papers, which were subject of a detailed analysis.Results: Many different approaches are proposed to foster technology transfer in software… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 83 publications
(131 reference statements)
0
12
0
Order By: Relevance
“…Empirical evidence is one of the proposed approaches in software engineering to transfer results from academia to industry. [ 47 ] Based on the results, we show that practitioners could see the UITD as a tool with potential to be put into practice because it requires little effort to be understood by people, regardless of their programming skill level.…”
Section: Discussionmentioning
confidence: 98%
“…Empirical evidence is one of the proposed approaches in software engineering to transfer results from academia to industry. [ 47 ] Based on the results, we show that practitioners could see the UITD as a tool with potential to be put into practice because it requires little effort to be understood by people, regardless of their programming skill level.…”
Section: Discussionmentioning
confidence: 98%
“…However, only few report what practitioners expect from researchers to adopt their technology 12 . To add to this body of knowledge, this article continues an avenue of research into software engineering technology transferpreviously reported in Reference 13. Therein, we have reported a systematic literature review on approaches, success factors, and barriers for software engineering technology transfer.…”
Section: Introductionmentioning
confidence: 84%
“…We aim to investigate what is considered important for software engineering technology transfer from an industry perspective and thereby complement our theoretical findings published inReference 13. Therefore, it is evaluated whether the findings from Reference 13 hold for the interviewed industry professionals.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…If training is provided in a fashion that brings with it valued knowledge and skills, including potential career opportunity and status, it can be particularly important in motivating employee commitment to both the organization and the change (Colquitt, LePine, & Noe, 2000; Martins & Kellermanns, 2004). Past research has shown that relevant training increases the individual’s use of new technology (Brings, Daun, Brinckmann, Keller, & Weyer, 2018; Gegenfurtner, Quesada-Pallarès, & Knogler, 2014). We hypothesize that change-related training will increase employee skills and knowledge relevant to the change.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%